Quality of life in patients with chronic obstructive pulmonary disease - Pineda Higuita, Sonia Elena; Ramos Melchor, Vidal de Jesús; Cadavid Carmona, Daniela (Universidad y Salud, 2016)
Objective: To describe the quality of life of patients with chronic obstructive pulmonary disease 2014. Materials and Methods: A descriptive observational cross-sectional study was performed to evaluate the quality of life of patients older than 65 and who had a diagnosis of chronic obstructive pulmonary disease. The sample corresponded to 179 users of ESE Metrosalud (Medellín), who agreed to participate voluntarily in the study. A structured survey that included socio-demographic variables, some environmental and social determinants, and aspects related to the disease was applied. Besides, the Saint George quality of life scale was also included, which is composed of three dimensions: symptoms, activities and impact. Results: The surveyed patients were between 65 and 99 years old, when they took the Saint George quality of life questionnaire, the most impacted dimension was the activity; it was obtained a statistically significant association between total quality of life and the level of schooling (P= 0.005), ethnic group (P= 0.004), and some variables related with the disease. Conclusions: There is an association between the quality related with health, according to the evaluation of the SGRQ and the extent of the disease.